Pemaknaan Audiens terhadap Dollification Tokoh Utama Perempuan dalam Serial Drama Korea Goblin - Umi Anizah, Nur; Dwiningtyas, Hapsari (Interaksi Online, 2017)
Goblin is one of the most popular South Korean drama series in the end of 2016 until the beginning of 2017. In the middle of its popularity, Goblin got several critiques for showing love story between a high school girl with an adult man and being judged strengthening the stigma of weak woman who needs man. Characterization of the heroine as high school student that is cute, young, and cheerful indicate the existence of dollification. This research focus on the use of fantasy theme analysis to see fantasy chain of Indonesian audience on the reception of dollification issue against heroine in Goblin drama.The main theory that being used in this research is Symbolic Convergence Theory. Collecting data technique was conducted by text analysis, focus group discussion, and indepth interview. The research was conducted to six audience of Goblin drama. The result of the research showed there are drawing and also losing fantasy chain on dollification theme. Drawing fantasy chain being identified through audience interpretation against appearance, youth soul, and sexuality of Ji Eun Tak as the heroine. On the appearance aspect, audience said that woman will be more attractive when physically looked young and thin. On the feminine appearance, female audience see femininity as value added of women’s beauty, meanwhile, male audience were not assume femininity as parameter of beauty. On the youth soul aspect, most of informants prefer the woman in a young demeanor so they can be protected by man in a relationship. While, on the sexuality aspect, informants interpret dollification of Ji Eun Tak as a form of power whose own by woman to decrease male domination. That power is interpreted positively by female audience, but it is interpreted negatively by male audience. Losing of fantasy chain happens when audience interpret text based on feminism perspective and the acceptance of dollification by male audience in this research. Drawing or losing of fantasy chain caused by several factors such as perspective of individual differentiation (sex, dating experience) and social category perspective of Korean drama fans group.